Association between Grit and Burnout among Clinical Medical Students - Nirucha Thamwiriyakul; Supitcha Thamissarakul; Prakasit Wannapaschaiyong (Siriraj Medical Journal)
Objective: The purpose of this study was to determine the relationship between grit and burnout among clinical medical students.